MODEL PERANCANGAN SISTEM TERDESENTRALISASI UNTUK KEAMANAN DATA GENETIKA MANUSIA BERBASIS BLOCKCHAIN DAN IPFS - Tri Stiyo Famuji; Alya Masitha; Maulana Muhammad Jogo Samodro; Galih Pramuja Inngam Fanani; Yuniariana Pertiwi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
The rapid development of genomic technology has heightened the urgency to address vulnerabilities in centralized systems managing sensitive human genetic data. This study proposes a decentralized system integrating blockchain and IPFS to enhance data security, integrity, and accessibility. Blockchain ensures immutable audit trails and dynamic access control via smart contracts, while IPFS provides scalable off-chain storage using cryptographic hashes (CIDs). The hybrid design separates raw data storage (encrypted via homomorphic encryption) on IPFS from access management on the Ethereum blockchain. A user interface built with React.js and Web3.js enables encrypted data uploads, role-based access requests, and real-time audit monitoring, complying with GDPR/HIPAA standards. Testing demonstrated the system’s effectiveness in preventing unauthorized access and ensuring data traceability. Challenges such as energy efficiency and regulatory compliance were addressed through sharding, layer-2 protocols, and selective data deletion mechanisms. This framework supports secure cross-institutional collaboration in genomic research, promoting public participation and accelerating biomedical innovation. Future work will focus on optimizing computational efficiency and expanding datasets.